Workshop Resensi Buku: Menguatkan Kemampuan Menulis Mahasiswa Dan Staf Perpustakaan UIN Gusdur - Prayogi, Arditya; Asirah, Khusnu; Maulida, Roslina; Anggana, Ridho Aji (STAI Publisistik Thawalib Jakarta, 2023)
Community service activities are carried out to strengthen writing skills, especially writing reviews. Service activities are carried out by way of workshops which are delivered with presentation techniques explaining the material. Presentation of the material is done using the lecture method, discussion-question-answer, and assignments. The results of the workshop activities: the activity participants have a good understanding of the material presented and have basic skills related to review writing efforts. This activity also has a social impact based on the good response given by the activity participants as well as the results of reviews that have been well assessed.